A comprehensive evaluation on quality of life for persons living on enteral nutrition and/or parenteral nutrition - Tamayo, Juliana (Kansas State University, 2021)
Enteral and parenteral nutrition remain the two nutrition support therapies for those individuals that are unable to meet the nutritional needs orally. Enteral nutrition utilizes a feeding tube to deliver nutrition to the stomach or small intestine. Parenteral nutrition bypasses the gastrointestinal tract and uses the central vein to deliver a specialized formula for nutrition. Because of the invasive nature of feeding tubes, central catheters, and peripherally inserted central catheter (PICC) lines, enteral nutrition (EN) and parenteral nutrition (PN) often result in physical and emotional problems for the individual. While there is evidence to suggest that both EN and PN are helpful in reducing malnutrition, there is limited data on the quality of life of persons undergoing EN and/or PN. This report explored the main themes that affect the quality of life of these individuals. Study results show that persons undergoing EN and/or PN have mixed emotions regarding their feeding tubes, central catheters, or PICC lines, and what the nutrition support therapy may bring to their lives. While participants admitted to having regained some quality of life thanks to increased nutrition, there was a clear decrease to quality of life due to emotional, physical, and/or economic factors. The findings suggest that that the emotional burden, physical discomfort, isolation, and economic costs of EN and/or PN are likely to impact the quality of life of the individual undergoing these nutritional support therapies.
Keywords: Enteral nutrition; Parenteral nutrition; Nutrition support therapy; Quality of life; Feeding tubes; Catheter